The Effect of Interactive Blended-Problem Based Learning Assisted Virtual Classroom on Critical Thinking Skills of Students of The Society Era 5.0 - Islam, Muhammad Naufal; Sumarmi, Sumarmi; Putra, Alfyananda Kurnia; Sugiyati, Pratiwi; Salsabilah, Sabrina (Indonesia University of Education, 2021)
Students in society 5.0 era education are directed to have adaptive and reactive response patterns to change through effective synergy as domain systems inaccessibility to technology in developing their skills actively and independently through critical thinking skills. Critical thinking skills as a cognitive domain in identifying, analyzing, and thinking of practical and creative ways to solve problems are needed to develop in the era of global society 5.0. Therefore, teachers are required to design learning processes that can accommodate student competencies in the era of society 5.0, one of which is the implementation of the innovative Interactive Blended Problem-Based Learning (IBPBL) learning model. This study aims to determine the effect of Interactive Blended Problem-Based Learning (IBPBL) assisted by Virtual Classroom on students' critical thinking skills. This type of research is a quasi-experimental study using a posttest-only control group design. The sample in this study used 72 students in class X IPS 2 (n = 36 control class) and X IPS 3 (n = 36 experimental class), Specializing in Social Sciences, SMAN 1 Tempeh, Lumajang Regency, East Java. The data analysis technique used the independent t-test hypothesis test to determine the significance value of the difference in the average treatment given to both the control and experimental classes. The results showed an effect of Interactive Blended Problem-Based Learning (IBPBL) assisted by Virtual Classroom on the critical thinking skills of students with Sig. (2-tailed) 0.000.